Extranodal extension is a criterion for poor outcome in patients with metastatic nodes from cancer of the nasopharynx. (January 2019) - Ai, Qi-Yong; King, Ann D.; Poon, Darren M.C.; Mo, Frankie K.F.; Hui, Edwin P.; Tong, Macy; Ahuja, Anil T.; Ma, Brigette B.Y.; Chan, Anthony T.C.
Highlights: Extranodal extension (ENE) is an indicator of outcome in nasopharyngeal cancer (NPC). Advanced ENE infiltrating to adjacent muscle/skin/salivary glands associated with poor outcome in NPC. Patients with advanced ENE presented similar poor outcome to those with N3 disease. Study suggested advanced ENE should be included in future staging of NPC. Abstract: Purpose: Extranodal extension (ENE) is a criterion for advanced nodal staging of oropharyngeal and hypopharyngeal carcinoma. Our aim was to determine if ENE should be a staging criterion for nasopharyngeal carcinoma (NPC). Materials & methods: MRI of 546 NPC patients were reviewed retrospectively and in 404/546 (74.0%) with metastatic nodes, the nodes were assessed for ENE (grade 0 = absent; grade 1 = infiltration of surrounding fat; grade 2 = infiltration of muscle/skin), size (total volume), site (unilateral/bilateral and upper/lower neck) and necrosis. Associations between nodal features and regional relapse free survival (RRFS), distant metastases free survival (DMFS) and overall survival (OS) were assessed using cox regression. Differences of survival rates were compared using log-rank test. A p-value of < 0.05 indicates statistical significance. Results: ENE grade was the only determinant of RRFS (p = 0.014) and only independent determinant of DMFS (p = 0.003) and OS (p < 0.001). Grade 2 ENE was associated with significantly poorer RRFS, DMFS and OS compared to grade 0 and 1 (p < 0.05). Addition of grade 2 ENE to N1 and N2 disease showed similar poor RRFS, DMFS and OS to N3 disease (p > 0.05). Compared to the current stage N3 disease, inclusion of grade 2 ENE increased the number of N3 patients from 53/546 (9.7%) to 82/546 (15.0%) with similar hazard ratios for DMFS (6.855 and 7.125, respectively) and OS (3.614 and 4.085, respectively). Conclusion: Grade 2 ENE (into muscle and/or skin and/or salivary glands) is an independent indicator of poor outcome and may be considered as a new criterion for N3 nodal disease in NPC.